UPAYA INDIA DALAM INTERNASIONALISASI EKONOMI PERDAGANGAN DI KAWASAN TIMUR LAUT INDIA - Nikiki, Suci Dwi; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is the study of international political economy which discussed the efforts of the central government of Indian in accelerating economic development in the Northeast region of India through internationalization of trade economy. Internationalization is the increased interaction between countries, especially in international business transactions such as exports or foreign direct investment.The author uses the liberal perspective in International Relations through international trade theory by Heckscer-Ohlin In India's efforts to increase economic development in the Northeast region, the author uses the concept of Economic Internationalization and Paradiplomacy.The level of analysis from the researc isi nation state. The central government made the North Eastern Region Viction (NERV) vision in 2020 as a form of mediating actor by the Sub National Government (SNG) with the central government of India. Ministry of Development of North Eastern Region making agent for develop economic in Norteast Region and expore natural resources primary from of horticultural and hydropotencial.One of the benefits of economic internationalization of this trade is the increased of Gross Domestic Product Revenue states of the Northeast region increased to 8,18% and internationalize trade economy with neighboring countries (Bangladesh, Myanmar, China, Bhutan) through the Land Custum Station( LCS) and established economic cooperation with ASEAN.Keywords : internasionalisation, paradiplomacy, Sub National Government, North Eastern Region Viction (NERV), Land Custum Station